Karakteristik Sel Punca Mesenkim yang Berasal dari Tali Pusat (Umbilical Cord Derived Mesenchymal Stem Cell/UCMSC) dari Macaca fascicularis dan Sekretomnya dalam Kondisi Hipoksia - Dumingan, Alvian; Malik, Amarila; Rinendyaputri, Ratih; Utama, Hieronimus Adiyoga Nareswara; Sunarno, Sunarno; Purwaningtyas, Yoggi Ramadhani; Idrus, Hasta Handayani; Noverina, Rachmawati; Huda, Fathul; Faried, Ahmad (Universitas Islam Negeri Mataram, 2024)
Mesenchymal Stem Cell (MSC) secretome has potential as a neuroprotective and neuroregenerative agent. It can have effects due to its paracrine factors, such as Brain Derived Neurotrophic Factor (BDNF) and Stromal-Cell Derived Factor-1 (SDF-1) which can be induced with hypoxia preconditioning. This compound may play a role in the treatment of neurological diseases. Stroke has become a neurological disease that contributes to high rates of mortality and morbidity worldwide. There have been several pre-clinical trials on animal stroke models using MSC secretomes from rats and humans, but no studies have been conducted on Non-Human Primate, such as Macaca fascicularis. This species has been widely used in biomedical research and part of it can be utilized for such studies which will reduce the cost of using human MSC. The results of this study, Umbilical Cord (UC)-MSCs of Macaca fascicularis have been successfully cultured and characterized in terms of phenotypic and differentiation. Hypoxia precondition was able to induce BDNF secretion up to 264 pg/mL and SDF-1 up to 666 pg/mL in the UCMSC secretome. Hypoxic preconditioning with 3% oxygen can induce the most optimal BDNF and SDF-1 secretion, compared to 1% and 5% hypoxia.